Siedlungsstruktur, Distanz und Lebensraum.: Funktionsräumliche Maßstabsvergrößerungen in einer westmittelfränkischen Region - ein unaufhaltsamer Trend? - Kunst, Friedemann (ERDKUNDE, 1985)
The fundamental social and economic changes of rural life during the past decades have at the same time changed the functional structure of the rural settlement pattern. The terms centralization, deconcentration and spatial separation of functions are being used in order to describe the distinct but interconnected developments in the settlement structure. So far they have been accepted or even fostered by public policy measures. However, in less populated rural areas especially these spatial changes have resulted in a considerable increase in distances and consequently aggravated the problem of access to working places, schools and other services. In contrast to densely populated areas a socially corrective public transport system is widely missing. In a case study in a rural Bavarian region considerable functional concentration, but at the same time, desintegration can be demonstrated for the period between1960 and1980. The deterioration of functional allocation, brought about especially by the functional losses of small places, has resulted in a rather general deterioration of the distance structure. In other words: the expenses in time and finance to overcome space have increased. It can be proved by empirical analysis of the traffic behaviour in the respective area that less mobile groups of the population in small places react either by refusing to select between destinations or by giving up trips altogether. Thus social inequalities are enhanced considerably by spatial inequalities. These findings lead to the conclusion that a revision of traditional concepts of rural spatial organization may be advisable. Taking he area of the case study as an example, a distribution model of spatial functions is developed which takes the potential activity space of less mobile rural residents into consideration. Calculations show that the observed trends can be effectively halted, on the premise that existing decentralization potentials in social infra structure can be mobilized.